Outbreak of Salmonella enteritidis gastroenteritidis: Investigation by pulsed field gel electrophoresis - Thong, Kwai Lin; Puthucheary, S.D.; Pang, T. (Elsevier, 1998)
Pulsed-field gel electrophoresis (PFGE) was used to investigate an outbreak of gastroenteritis caused by Salmonella enteritidis. The outbreak occurred among university undergraduates who consumed contaminated food. Molecular typing was done by analyzing DNA band patterns of isolates of S. enteritidis after digestion of chromosomal DNA with infrequently-cutting restriction endonucleases Xbal,Avrll, and Spel and separation of DNA fragments using PFGE. Twentv-nine outbreak isolates of S. enteritidis had identical or highly similar PFGE patterns, whereas different PFGE patterns were observed among three epidemiologically-unrelated isolates obtained durinq the same period. The data obtained confirm the value of PFGE in epidemiologic investigations of outbreaks caused by S. enteritidis.